2019
DOI: 10.1111/1751-7915.13359
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of bacteriorhodopsins in Haloarchaeal species isolated from Indian solar salterns: deciphering the role of the N‐terminal residues in protein folding and functional expression

Abstract: Summary Interesting optical and photochemical properties make microbial rhodopsin a promising biological material suitable for various applications, but the cost‐prohibitive nature of production has limited its commercialization. The aim of this study was to explore the natural biodiversity of Indian solar salterns to isolate natural bacteriorhodopsin ( BR ) variants that can be functionally expressed in Escherichia coli . In this study, we report the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…The partial 16S rRNA sequences for pws2, pws4, and pws10 shared 100% identity score with Haloarcula salaria JCM 15759, Haloarcula japonica JCM7785 and Halomicrobium mukohataei JP60, respectively ( Table 1 ). All the isolates were further screened for the presence of the bop using degenerate primers (DegF and DegR) as reported earlier (Verma et al, 2019 ) ( Supplementary Table 1 ). The presence of an expected 450 bp PCR product on an agarose gel confirmed that all the strains except pws11 were positive for bop ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The partial 16S rRNA sequences for pws2, pws4, and pws10 shared 100% identity score with Haloarcula salaria JCM 15759, Haloarcula japonica JCM7785 and Halomicrobium mukohataei JP60, respectively ( Table 1 ). All the isolates were further screened for the presence of the bop using degenerate primers (DegF and DegR) as reported earlier (Verma et al, 2019 ) ( Supplementary Table 1 ). The presence of an expected 450 bp PCR product on an agarose gel confirmed that all the strains except pws11 were positive for bop ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The protein sequence comparison shows that pws5-BR (locus tag -NLV14165.1) shares 92% sequence identity with H. marismortui BRI (HmBRI). Based on our previous study (Verma et al, 2019 ), we chose the pET22b expression vector to yield recombinant protein with C-terminal 6× His-tag for affinity purification. BR is a leaderless membrane protein and putting N-terminal affinity tag may interfere with the membrane localization and protein folding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three strains were isolated from solar saltern samples collected from Marakkanam solar salterns, India (12°11′13.0272″N and 79°55′40.4220″E) using the dilution-plate technique on the Halovibrio agar medium as described previously ( Verma et al, 2019 ). Briefly, on agar plates, the reddish-pink opaque convex colonies, 1–2 mm in diameter appeared in 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…The protein sequence comparison shows that pws5-BR (locus tag -NLV14165.1) shares 92% sequence identity with H. marismortui BRI (HmBRI). Based on our previous study (Verma et al, 2019), we chose the pET22b expression vector to yield recombinant protein with Cterminal 6× His-tag for affinity purification. BR is a leaderless membrane protein and putting N-terminal affinity tag may interfere with the membrane localization and protein folding.…”
Section: Expression and Purification Of Recombinant Pws5-brmentioning
confidence: 99%